PENGAWETAN BAMBU TALANG SECARA SEDERHANA - Eka Novriyanti; Edi Nurrohman 2) (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
This research was conducted to examine the effectiveness of preserving bamboo with a Boron compound preservative. Four levels of concentrations, i.e 5, 10, 15, and 20% were tested through simple method on bamboo talang (Schizostachyum brachycladum). Lower part of each culm was cut and debarked prior to one week soaking in the boric solution. Results indicated that longitudinal penetration could reach 100%. Retention was varied in accord with boric concentration, but the 15%solution gave the highest retention.